Ethnic, cultural and civic identities in Ancient coinage of the South of the Iberian Peninsula (3rd C. BC -1st C. AD) - Mora-Serrano, Bartolomé; Cruz-Andreotti, Gonzalo (British Archaeological Reports, 2012)
Behind the complex systematisation of the coinage from Ulterior lie relevant contributions to the ethnocultural mapping of the region. This paper explores the possibility, as in the case of Phoenician-Punic coinage, of using numismatic evidence from Turdetani, Turduli, Oretanos, and Bastetano cities to identify distinct cultural realities – enhanced or not by Roman presence in the region. It further questions whether these realities correspond with maps based on previous studies on place names, archaeological remains and ancient geographical references.
Keywords: España - Historia - <....-0414 (Edad antigua); Etnología; Turdetanos; Península ibérica en la antigüedad; Numismática; Turdetania; Bastetania; Oretania; Túrdulos; Identidad; Romanización; Fenicios; Púnicos